Democracy in Pakistan: Problems and Prospects in Making Informed Choices - Waqas, Muhammad; Khattak, Muqaddas (International Journal of Social Sciences and Management, 2017)
Democracy is a form of government which supports extensive participation of people in government and also promotes the views of citizens for the smooth functioning of society. The form of Democracy in Pakistan is one of the best and unique democracies in the world but unfortunately its future is bleak due to the non observance of what is actually the true essence of democracy, the informed choices. The main reasons that informed choices are not made is due to the unawareness of the people about the form of democracy in Pakistan, flawed political culture, and legal pluralism. Int. J. Soc. Sc. Manage. Vol. 4, Issue-1: 9-11